2019
DOI: 10.2166/wst.2019.295
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization and oxidation of phenols in supercritical water

Abstract: The treatment of toxic and difficult-to-degrade phenolic compounds has become a key issue in the coking, pharmaceutical, and chemical industries. Considering the polymerization and oxidation of phenolic compounds in supercritical water partial oxidation/supercritical water oxidation (SCWPO/SCWO), the present study reviewed the removal efficiency and reaction pathway of phenolic compounds and phenolic waste/wastewater under different reaction conditions. Temperature is the dominant factor affecting the SCWO rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Thereafter, an OH • free radical was added to the α carbon of the aromatic ring and converted to phenol by oxidation, decarboxylation, and hydroxylation. As the most important intermediate product, phenol, whose hydroxyl group affects the ring-opening process, produces many undesirable polymerization products, such as dibenzofuran and diphenyl oxide. , In addition, p-benzoquinone was also an intermediate product of phenol in the oxidation atmosphere. P-benzoquinone and other benzene-containing substances were further oxidized to open the ring to form low molecular carboxylic acids (such as acetic acid) and aliphatic hydrocarbon organic radicals. These low-molecule compounds would recombine to produce long-chain fatty acids and aliphatic hydrocarbons, , both of which were detected in the liquid products, and eventually oxidized to CO 2 and H 2 O …”
Section: Degradation Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, an OH • free radical was added to the α carbon of the aromatic ring and converted to phenol by oxidation, decarboxylation, and hydroxylation. As the most important intermediate product, phenol, whose hydroxyl group affects the ring-opening process, produces many undesirable polymerization products, such as dibenzofuran and diphenyl oxide. , In addition, p-benzoquinone was also an intermediate product of phenol in the oxidation atmosphere. P-benzoquinone and other benzene-containing substances were further oxidized to open the ring to form low molecular carboxylic acids (such as acetic acid) and aliphatic hydrocarbon organic radicals. These low-molecule compounds would recombine to produce long-chain fatty acids and aliphatic hydrocarbons, , both of which were detected in the liquid products, and eventually oxidized to CO 2 and H 2 O …”
Section: Degradation Mechanismmentioning
confidence: 99%
“…As the most important intermediate product, phenol, whose hydroxyl group affects the ring-opening process, produces many undesirable polymerization products, such as dibenzofuran and diphenyl oxide. , In addition, p-benzoquinone was also an intermediate product of phenol in the oxidation atmosphere. P-benzoquinone and other benzene-containing substances were further oxidized to open the ring to form low molecular carboxylic acids (such as acetic acid) and aliphatic hydrocarbon organic radicals. These low-molecule compounds would recombine to produce long-chain fatty acids and aliphatic hydrocarbons, , both of which were detected in the liquid products, and eventually oxidized to CO 2 and H 2 O …”
Section: Degradation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, long-term discharge and treatment difficulties of phenolic wastewater could lead to more discharge of industrial waste on the water surface that is a serious problem for not only the human health but also the ecosystem. However, an alternative strategy should be adopted to treat phenolic wastewater (Pillai & Gupta 2016 , Zhang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that SCWO can mineralize organics in a very short time by turning water into an excellent solvent at critical pressure (22.1 MPa) and temperature (374°C). The researchers have investigated the degradation of ammonia (Bermejo et al 2008), phenolic compounds (Zhang et al 2019), pharmaceutical (Ma et al 2018;Mylapilli & Reddy 2019), organophosphate flame retardants (Yang et al 2019) and pesticides (Xu et al 2015) by the SCWO process. However, although PAHs are characterized as mutagenic or carcinogenic pollutants, a few studies (Onwudili & Williams 2007;Xu et al 2013;Ates & Argun 2021) on the SCWO of PAHs were found in the literature.…”
Section: Introductionmentioning
confidence: 99%